(untitled) (Linguistics in Amsterdam, 2012)
In this paper the results of an investigation of word order in Russian Sign Language (RSL) are presented. A small corpus (16 minutes) of narratives based on comic strips by 9 native signers was analyzed and a picture-description experiment (based on Volterra et al. 1984) was conducted with 6 native signers. The data reveal that the most frequent word order in RSL is SVO for plain and agreeing verbs and SOV for classifier predicates. Some factors can influence the word order, namely aspect marking on the verb (favours OV), semantic reversibility of the situation (favours SVO) and “heaviness” (manifested in the presence of modifiers) of the object (favours VO). One of the findings of the investigation is that locative situations are described differently in the narratives and in the experimental settings: in the latter but not in the former case the OSV order is quite common. This may result from two different strategies of creating locative sentences: syntactic vs. spatial strategy. Doubling of constituents is common in RSL discourse: verbal and nominal predicates, arguments, adverbs, adjectives, and even whole sentences can be repeated, the second occurrence of the constituent usually being more morphologically, prosodically or semantically marked.